Determinants of stunting among 0–59 months children in Lesotho: A multilevel analysis of 2023/24 Demographic and Health Survey - Lencho Kajela Solbana; Firezer Belay Keno; Atoma Negera; Baru Legesse Kejela; Markos Desalegn; Emiru Merdassa (PLoS ONE, 2026)
Background Stunting is height for age below minus 2 standard deviations of the World Health Organization standard. It affected more than one-third of children in Lesotho. Few studies applied multilevel model to identify individual, household, and community-level determinants. This study aimed to assess the prevalence and multilevel determinants of stunting among children aged 0–59 months in Lesotho using data from the 2023/24 Demographic and Health Survey. Methods We included a weighted 1,488 children aged 0–59 months across 400 enumeration areas. The weighted prevalence of stunting was determined. Individual and community level determinants of stunting were identified at a 0.05 level of significance. Models were compared using Akaike Information Criterion (AIC), Intraclass Correlation Coefficient (ICC), and Proportional Change in Variance (PCV). Results Prevalence of stunting was 35.59% (95% CI: 33.20–38.06). Its determinants were male (AOR = 1.41; 95% CI: 1.09–1.82), age 12–23 months (AOR = 2.44; 95% CI: 1.48–4.14) and 24–59 months (AOR = 1.98; 95% CI: 1.20–3.24), 4–7 birth order (AOR = 1.43; 95% CI: 1.01–2.03), and poor (AOR = 2.58; 95% CI: 1.85–3.59) and middle wealth index (AOR = 2.03; 95% CI: 1.37–3.03). Qacha’s Nek, Thaba-Tseka, Mohale’s Hoek, and Quthing have a higher prevalence of stunting. Conclusion 35.59% of children 0–59 months in Lesotho are stunted. Its determinants were male, age 12–23 and 24–59 months, poor and middle wealth, and higher birth order. Ministry of Health, Non-governmental organizations, and community health workers should therefore strengthen age-specific, equity-driven nutrition programs.